Secularism in historical perspective (New Delhi, 2004)
When the word 'Secular' was borrowed from the west and placed into the preamble of our constitution by the founding members of modern India, the message they wanted to send out to the world and the value system they wanted to instill among Indians in a nutshell was that India will have no state religion, all the people
Keywords: Secularism